The genome sequence of the Seraphim, Lobophora halterata (Hufnagel, 1767) [version 1; peer review: 2 approved] - Douglas Boyes; Peter W.H. Holland (Wellcome Open Research, 2022)
We present a genome assembly from an individual female Lobophora halterata (the Seraphim; Arthropoda; Insecta; Lepidoptera; Geometridae). The genome sequence is 315 megabases in span. The complete assembly is scaffolded into 32 chromosomal pseudomolecules with the Z and W sex chromosomes assembled. The mitochondrial genome has also been assembled and is 15.7 kilobases in length.